Paste Tailings Management - Yilmaz, Erol; Fall, Mamadou (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of paste tailings disposal at mine sites. It deals comprehensively with the characterization of sulphide-rich tailings, geotechnical and microstructural behaviour, surface tailings disposal applications, underground paste backfilling, and case studies. The authors place emphasis on the characterization, monitoring, disposal and treatment, as well as environmental considerations of problematic sulphidic tailings. The framework is supported by worldwide case studies.- Resumé vydavatel
Keywords: hlušina; odpadové hospodářství; ložisková geologie; mining waste; waste management; economic geology; elektronické knihy; sborníky; electronic books; papers of several authors